2018
DOI: 10.1371/journal.pone.0191515
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA oligonucleotides with base mutations by terahertz spectroscopy and microstructures

Abstract: DNA oligonucleotides with a 5-base mutation at the 3'-terminus were investigated by terahertz (THz) spectroscopy in a marker-free manner. The four single-stranded oligonucleotides with 17nt have been detected with specificity on a microfluidic chip, and corroborated by spectral measurements with split-ring resonators. The number of hydrogen bonds formed between the oligonucleotide and its surrounding water molecules, deemed a key contribution to the THz absorption of biological solutions, was explored by molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…From Figure 3a, we can see that the absorption coefficient of the Gly23 solution increases with the increase of the frequency and there is no prominent fingerprint signal; observations which are in good agreement with the THz spectra of most biomolecular solutions [32,43,44,45]. In Figure 3b, it can be seen that the absorption coefficient of the Gly23 solution decreases with the increase of the degree of confinement at different frequencies.…”
Section: Resultssupporting
confidence: 74%
“…From Figure 3a, we can see that the absorption coefficient of the Gly23 solution increases with the increase of the frequency and there is no prominent fingerprint signal; observations which are in good agreement with the THz spectra of most biomolecular solutions [32,43,44,45]. In Figure 3b, it can be seen that the absorption coefficient of the Gly23 solution decreases with the increase of the degree of confinement at different frequencies.…”
Section: Resultssupporting
confidence: 74%
“…Consequently, molecules such as amino acids (and urea as a metabolite), nucleosides, nucleotides and nucleic acids are investigated by the THz community. The characteristics of these molecules, such as temperature-dependent absorption spectra [28,48], the dielectric response of molecular solutions such as completely solvated mono-and oligonucleotides [7,51,68,119,146,155,[160][161][162], modifications of the molecular structure and spectral signatures as a function of both the polarization state of incident radiation [52] and the hydration level [94], have been reported.…”
Section: Subject Of Thz Studiesmentioning
confidence: 99%
“…THz spectroscopy was used for the qualitative and quantitative analysis of various types of nucleic acids. It was shown that when the qualitative composition of the DNA chain is changed by one nucleotide, the spectral properties of the DNA molecule is changed in the THz range that indicates the possibility of detecting DNA point mutations using THz spectroscopy [48]. This potential of THz technology may be extremely useful for intraoperative diagnosis of brain tumors.…”
Section: Determination Of Molecular Characteristics Of Tumorsmentioning
confidence: 99%